1983
DOI: 10.1254/jjp.33.113
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular effects of dobutamine, dopamine and isoproterenol on the whole animal and isolated cross-perfused atrium in dogs.

Abstract: Abstract-The right atrium of the dog was isolated and cross-perfused with arterial blood of another (donor) dog anesthetized with pentobarbital. When dobutamine, dopamine or isoproterenol was administered intravenously to the donor dog, the following changes were elicited in them: Dobutamine caused slight biphasic changes in heart rate. Dopamine induced biphasic changes in blood pressure and heart rate. Isoproterenol produced a decrease in blood pressure and a marked increase in heart rate. All these 3 catecho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
1992
1992

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…These results suggest that etilefrine is a highly selective 13-1 adrenergic agonist like dobutamine. From our laboratory, Chiba et al [31] and Akahane et al [15] reported that the potency of dobutamine, i.e., sinus rate ED (40%) and atrial tension ED (100%) were 4.1-5.6nmol and 1.6-1.8nmol, respectively, in the atrial preparations, and ventricular tension ED (100%) was 5.1nmol in the ventricular preparations. Therefore, etilefrine is 5 times less potent than dobutamine in chronotropism and 7-16 times less potent than dobutamine in inotropism.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that etilefrine is a highly selective 13-1 adrenergic agonist like dobutamine. From our laboratory, Chiba et al [31] and Akahane et al [15] reported that the potency of dobutamine, i.e., sinus rate ED (40%) and atrial tension ED (100%) were 4.1-5.6nmol and 1.6-1.8nmol, respectively, in the atrial preparations, and ventricular tension ED (100%) was 5.1nmol in the ventricular preparations. Therefore, etilefrine is 5 times less potent than dobutamine in chronotropism and 7-16 times less potent than dobutamine in inotropism.…”
Section: Discussionmentioning
confidence: 99%